Cultivating Knowledge and Health: Empowering Students with Medicinal Plant Education at SDN Kedunghalang 03 Bogor - Supriadi, Yusuf (Journal of Social and Community Development, 2024)
This community service project, conducted at SDN Kedunghalang 03 Bogor, aimed to educate fifth-grade students about Family Medicinal Plants (Tanaman Obat Keluarga or TOGA). The event, held in the school's auditorium, included presentations, discussions, and interactive games using audiovisual aids, followed by a hands-on planting session. Led by a lecturer and six students from the Bumi Siliwangi Bandung Academy of Pharmacy, the program sought to instill knowledge about the types, benefits, and cultivation methods of medicinal plants. The students' enthusiastic participation highlighted the success of the initiative, fostering a deeper understanding and appreciation for TOGA. The practical sessions, which involved planting, fertilizing, and caring for medicinal plants, were complemented by demonstrations of how to process these plants into healthy drinks. The program not only enhanced the students' botanical knowledge and practical skills but also promoted environmental stewardship and health awareness within the school community. The involvement of the school principal and teachers further underscored the importance of the initiative, contributing to its overall success and lasting impact.